Relationship between Distraction and Academic Adjustment among First Year Undergraduate Students in Public Universities in Kenya - Agingu, Eunice Atieno; Owaa, Judith Anyango; Raburu, Pamela (Global Journal of Educational Studies, 2024)
First year undergraduate students (FYUS) arrive at the university having very different academic and social skills and from different backgrounds and cultures. Some students adjust easily and are set up for successful university study whereas others become disoriented from their studies, underperform academically or drop out completely. The current study explored the relationship between distraction during transition and academic adjustment among first year undergraduate students. The study was guided by Person-Centred and Schlossberg’s Transition Theory. The study population comprised 1,539 first year undergraduate students admitted at a public university in Kenya for the 2020/2021 academic year and 45 service providers. Stratified random sampling was used to select 306 students while purposive sampling was used to select 40 service providers for the study. Concurrent Triangulation Design was used within Mixed Methods Approach whereby data was collected using both quantitative and qualitative methods. Questionnaires for students and service providers together with interview schedules for service providers were employed. Focus Group Discussions were also held for 13 students divided into two groups. Internal consistency of the questionnaire yielded a Cronbach’s alpha α = .769. Quantitative data analysis was done on percentages, Pearson’s correlation and regression analyses using SPSS version 22 computer programme. Thematic Analysis approach was employed to analyse qualitative data. Results indicated a significant negative correlation between distraction and academic adjustment.